2010
DOI: 10.1007/s10535-010-0115-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering using mtlD gene enhances tolerance to water deficit and salinity in sorghum

Abstract: Sorghum bicolor L. Moench cv. SPV462 was transformed with the mtlD gene encoding for mannitol-1-phosphate dehydrogenase from E. coli with an aim to enhance tolerance to water deficit and NaCl stress. Transgene (pCAM mtlD) integration and expression were successfully confirmed by PCR, Southern, RT-PCR and Western analysis. Segregation analysis based on germination of T 0 seed on hygromycin-supplemented medium revealed an expected Mendelian ratio 3:1 in lines 5, 72 and 75. Retention of leaf water content was rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Table 3 indicate that there was an increase in detectable mannitol in all of the transgenic plants. Various other reports have also confirmed that the expression of mtlD in transgenic plants results in accumulation of mannitol, along with an improved drought and salt tolerance in different plant species including potato [41], sorghum [40], wheat [36], and canola [42].…”
Section: Salinity Tolerance Test Of Hva1mentioning
confidence: 80%
See 1 more Smart Citation
“…Table 3 indicate that there was an increase in detectable mannitol in all of the transgenic plants. Various other reports have also confirmed that the expression of mtlD in transgenic plants results in accumulation of mannitol, along with an improved drought and salt tolerance in different plant species including potato [41], sorghum [40], wheat [36], and canola [42].…”
Section: Salinity Tolerance Test Of Hva1mentioning
confidence: 80%
“…The mannitol dehydrogenase (MTLD) enzyme, encoded by the bacterial mtlD gene, is the key enzyme in mannitol metabolism, reversibly converting fructose-6-phosphate to mannitol-1-phosphate. The mtlD gene has been transferred to several crop species, resulting in certain cases in enhanced plant height, fresh and dry biomass weight, increase in salinity and/or drought tolerance, and often in accumulation of mannitol [32][33][34][35][36][37][38][39][40][41][42]. Research on transfer of bacterial RNA chaperones performed to induce abiotic stress tolerance in maize is among other promising research areas [43].…”
Section: Introductionsmentioning
confidence: 99%
“…1) whose synthesis are well characterised (e.g. Loescher and Everard 2000) and subject to many attempts to engineer stress tolerance Prabhavathi et al 2002;Maheswari et al 2010). Although these attempts lead to increased stress tolerance of the engineered plants, it has been questioned whether this can lead to a significant increase of whole-plant tolerance under field conditions (Bohnert and Shen 1998).…”
Section: Polyols Are a Major Carbon Sinkmentioning
confidence: 99%
“…More recently, transformation studies have focused primarily on using marker genes to establish, develop, and improve transformation and regeneration processes (Nguyen et al 2007). The production of transgenic sorghum with agronomic traits such as nutrient improvement, pest resistance, disease, and stress tolerance has been reported (Zhao and Tomes 2003;Gao et al 2005b;Maheswari et al 2010;Arulselvi et al 2011). Low transformation frequency and transgene silencing are limiting factors for sorghum varietal improvement by genetic engineering.…”
Section: Introductionmentioning
confidence: 99%